2020
DOI: 10.1007/s12253-020-00816-0
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Syndecan-1 in Cervical Cancers

Abstract: Syndecan-1, is a transmembrane heparan/chondroitin sulfate proteoglycan necessary for cell-cell and cell-matrix interactions. Its decreased level on the cell surface correlates with poor prognosis in several tumor types. Aberrant stromal localization of syndecan-1 is also considered an unfavorable prognostic factor in various human malignancies. In the presented work the question was addressed if changes in syndecan-1 expression are related to the prognosis of cervical cancer. Immunohistochemistry for syndecan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…A limitation to our in vitro model is the lack of stromal components, which could significantly influence the behavior of the tumor tissue. Ectopic expression of syndecan-1 in stromal cells has been reported in carcinomas of the cervix [ 95 , 96 ], and stromal syndecan-1 expression was shown to correlate with poor prognosis in some tumor types such as cancers of the stomach [ 97 ], pancreas [ 46 ], endometrium [ 98 ], oral cavity [ 99 ], breast [ 100 , 101 ], bladder [ 48 ], and ovary [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation to our in vitro model is the lack of stromal components, which could significantly influence the behavior of the tumor tissue. Ectopic expression of syndecan-1 in stromal cells has been reported in carcinomas of the cervix [ 95 , 96 ], and stromal syndecan-1 expression was shown to correlate with poor prognosis in some tumor types such as cancers of the stomach [ 97 ], pancreas [ 46 ], endometrium [ 98 ], oral cavity [ 99 ], breast [ 100 , 101 ], bladder [ 48 ], and ovary [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…33 It has been found that soluble SDC1 can be used for noninvasive diagnosis in patients with chronic toxic hepatitis, 34 and it is effective in predicting the prognosis of patients with multiple myeloma, cervical cancer and other malignant tumors. [35][36][37] However, little is known about SDC4 shedding. A previous study found that the genetic deletion of SDC4 altered the body composition, metabolic phenotype and function of metabolic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated a dysregulation of Sdc-1 expression in cervical carcinoma tissues (6,(13)(14)(15)(16)(17). To further investigate the clinicopathological relevance of aberrant Sdc-1 expression in this disease, we made use of large public gene expression datasets.…”
Section: Sdc-1 Is Highly Expressed In Cervical Carcinoma and Correlates With A Poor Overall Survivalmentioning
confidence: 99%
“…Thus, this protein has emerged as a novel target for the development of selective and more potent therapies. Although some studies indicate that Sdc-1 can act both anti-or pro-tumorigenic (13)(14)(15)(16)(17), the mechanisms by which Sdc-1 participates in the pathogenesis and progression of tcervical cancer are still unknown. In this study, we analyzed the dysregulation and prognostic impact of Sdc-1 expression in clinical specimens of cervical cancer utilizing publically available transcriptomic datasets.…”
Section: Introductionmentioning
confidence: 99%